Aportación al conocimiento de los hongos de la sierra de Collserola y zonas próximas (Catalunya), II - Tabarés Carriedo, Manuel; Rocabruna i Llavanera, August (Revista Catalana de Micologia, 2007)
Second contribution to the catalogue of fungi observed in Catalonian littoral mountains, in theCollserola forest (Barcelona) in the zone delimited in the map. We list 133 species composed byAscomycetes and Basidiomycetes. Some of them have a special interest: Lachnum clandestinum(Bull ex Mérat) Fuck. Pezize moravecii (Svréek) Donadini, Pterula multifida Fr. : Fr, Camarophyllopsis foetens (Phill.) Arnolds, Collybia racemosa (Pers. : Fr.) Quel, Cystolepiota sistrata(Fr. : Fr.) Sing. ex Bon a Bellu, Limacella glioderma (Fr.) Rarle Inocybe griseolilacina Lge.